WELDED CONNECTION OF ROD PARTS WITH BODY PARTS BY ELECTRO PERCUSSIVE WELDING - S.V. NESCOROMNIY (Advanced Engineering Research, 2009)
The welded joints of the type of rod parts and body part are applied in machine-building and building. To get such joints for nonferrous metals and alloys by arc welding is extremely difficult. For these purposes especially for welding large sized parts it would be advisable to use electro percussive welding with magnetic pulsed drive it combines thermal and forced influence on welded parts due to the condenser batteries charges on working tool inductor.